Optimal level of hypothermia for prolonged myocardial protection assessed by 31P nuclear magnetic resonance - Karck, Matthias; Vivi, Antonio; Tassini, Maria; Schwalb, Herzl; Askenasy, Nadir; Merchav, Hadar; Navon, Gil; Uretzky, Gideon (The annals of thoracic surgery, 1992)
The optimal level of hypothermia during myocardial preservation for cardiac transplantation is not known. Phosphorus 31 nuclear magnetic resonance spectroscopy was used to assess the effect of different preservation temperatures (15 °C in group 1, 4 °C in group 2) on the myocardial high-energy phosphate profiles during prolonged global ischemia and subsequent reperfusion of isolated rat hearts. Adenosine triphosphate depletion during ischemia was more gradual in group 2, leading to significant differences in myocardial adenosine triphosphate concentrations between the two groups after 3 hours of ischemia. The fall in intracellular pH during ischemia was significantly less pronounced in hearts preserved at 4 °C as compared with those at 15 °C. The postischemic recovery of both the left ventricular peak systolic pressure and the maximum rate of increase of left ventricular pressure was enhanced in group 2, although the ischemic period was 3 hours longer than in group 1. Hypothermia at 4 °C as compared with 15 °C appears to prolong myocardial protection with respect to adenosine triphosphate preservation, prevention of the fall in intracellular pH, and the enhancement of postischemic hemodynamic recovery.